Climate Change and Range Expansion of Protostrongylid Nematodes in the Canadian Arctic ... - Kafle, Pratap (Graduate Studies, 2018)
Through this doctoral research, I aimed to determine the diversity, distribution and abundances of protostrongylids in muskoxen and caribou from several sites in Subarctic and Arctic Canada and investigate the northward range expansion of Umingmakstrongylus pallikuukensis and Varestrongylus eleguneniensis in relation to Arctic warming. I first developed morphological keys to differentiate the first stage larvae (L1) of U. pallikuukensis, V. eleguneniensis and Parelaphostrongylus andersoni. This enabled me to identify L1 to the species level and determine the intensity of infections. Secondly, I analyzed over 1600 muskox and caribou fecal samples, and 40 muskox lung samples to determine the diversity, distribution and abundance patterns of protostrongylids. I found that the diversity and abundance of protostrongylids varied geographically. Both U. pallikuukensis and V. eleguneniensis had expanded their ranges and increased in abundance on Victoria Island between 2013 and 2017, with U. pallikuukensis expanding ...